Cooling Of Photovoltaic Panel Using Water-Cooled System - Siew, Teng Yi (Universiti Sains Malaysia, 2021)
Solar energy is one of the renewable energy resources that can be utilized to cater for the growing power supply demand worldwide. Solar energy can be harvested and converted into useful electrical energy via solar panel. Practically, the efficiency of solar panel is very low and it is affected by the heat accumulated on solar panel, transmitted through solar radiation. The high temperature on solar panel would affect the solar energy conversion of a solar panel. Despite the adverse effect of high temperature on solar panel, most of solar power industry does not use any cooling mechanisms to reduce the temperature on the solar panel, it is thus performing at low efficiency level. This prevents more energy that can be generated by the solar panel, producing lesser economic benefits. By integrating cooling system into solar panel, the excess heat can be removed and solar panel could operate at lower temperature range. In this study, a model of cooling system consists of copper tube and solar panel is simulated with ANSYS Fluent 19.2 using Solar Load Model and Heat Flux to simulate solar radiation. Based on solar radiation variation in a day, the effects of temperature and flow of water are thus studied. The temperature of the surface of solar panel can be reduced significantly. Different designs of cooling tubes are studied and the resulted performances are presented in this thesis.